Looking to aquatic species for conservation farming success - Rebecca R. Gentry (Conservation Letters, 2019)
Abstract Thousands of species worldwide are threatened with extinction due to human activities. For some animals, such as elephants, totoaba, and bluefin tuna, population declines are largely driven by hunting. High prices and large profits create a strong incentive for illegal hunting, even in the face of penalties and strict international restrictions against trade. One innovative solution to help reverse the declines of such species is to farm them to increase supply, thereby reducing prices and decreasing hunting incentives. However, this idea has been criticized as impractical, though some examples exist of successful implementation. Here, we evaluate the hurdles facing endangered species farming as a market‐based mechanism to reduce illegal harvest of wild populations and provide guidance on when it is most likely to be effective. Using a simple model, we show how farming costs and enforcement of anti‐poaching measures are key drivers of success for this solution. We also argue that many of the most promising candidates are aquatic species that have been largely overlooked. Thus, while conservation farming may not be a solution for all endangered species, it should be more seriously considered for species that could be produced quickly and cost‐effectively.